Spindle cell sarcoma of the uterine corpus with adipose metaplasia: expanding the morphologic spectrum of neoplasms with MEIS1-NCOA2 gene fusion - Kommoss, Felix; Kölsche, Christian; Mentzel, Thomas; Schmidt, Dietmar; Deimling, Andreas von; McCluggage, W. Glenn; Kommoss, Friedrich (International journal of gynecological pathology, 2022)
We report a spindle cell sarcoma arising in the uterine corpus of a 26-yr-old patient. The patient underwent a simple hysterectomy and the uterine corpus contained a 9 cm tumor showing nodular and “finger-like” myometrial invasion. Histologically, the tumor was composed of a monomorphic population of atypical spindle cells which contained widespread foci of cytologically benign adipocytes. Immunohistochemistry revealed diffuse strong positivity for CD10, CD56, and CD99 and diffuse weak positive staining with ER and WT1 while smooth muscle markers, S100, TLE1, and cyclin D1 were negative. Total RNA sequencing identified an in-frame fusion between exon 6 of MEIS1 and exon 12 of NCOA2. Copy number analysis revealed few aberrations with no deletions or amplifications identified. No adjuvant therapy was given and the patient is disease-free 9 yr after initial diagnosis. This case represents the second report of a uterine sarcoma harboring a MEIS1-NCOA2/1 gene fusion and expands the morphologic spectrum of recently reported spindle cell sarcomas arising in the genitourinary tract harboring MEIS1-NCOA2/1 gene fusions. This is the first reported case of such tumors with an adipocytic component.
Gesehen am 24.08.2022